Human perceptions of colour rendition vary with average fidelity, average gamut, and gamut shape. (December 2017) - Royer, MP; Wilkerson, A; Wei, M; Houser, K; Davis, R
An experiment was conducted to evaluate how subjective impressions of a light source's colour quality depend upon the details of the shifts it causes in the colour appearance of illuminated objects. Twenty-eight participants each evaluated 26 lighting conditions in a 3.1 m by 3.7 m room filled with objects selected to cover a range of hue, saturation, and lightness. IES TM-30-15 Fidelity Index ( R f ) values ranged from 64 to 93, IES TM-30 Gamut Index ( R g ) values ranging from 79 to 117, and IES TM-30 red chroma shift ( R cs, h1 ) values ranging from −19% to 26%. All lighting conditions had the same nominal illuminance and chromaticity. Participants were asked to rate each condition on eight point scales for saturated–dull, normal–shifted, and like–dislike, as well as classifying the condition as one of saturated, dull, normal, or shifted. The findings suggest that gamut shape is more important than average gamut area for modeling human preference, with red playing a more important role than other hues. Average fidelity alone is a weak predictor of human perception, especially CIE R a . Nine of the top 12 rated products had a CIE R a value of 73 or less, which indicates that the criteria of CIE R a ≥ 80 may be excluding many preferred light sources.